Implementasi Kebijakan Program Keluarga Harapan dalam Meningkatkan Kesejahteraan Keluarga Penerima Manfaat di Desa Curahmalang Kecamatan Rambipuji - Jourdy Sasena Arfindo; Imam Sunarto; Nur Aini Mayasiana (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This research was conducted in Curahmalang Village, Rambipuji District, with the aim of determining how the Family Hope Program (PKH) policy is implemented in improving the welfare of beneficiary families (KPM). PKH, as one of the conditional social assistance programs designed by the government, plays a strategic role in poverty alleviation efforts, so it is important to assess the extent to which this policy is effective at the village level. This research used a descriptive qualitative method with policy implementation indicators referring to the George C. Edward III model, which includes aspects of communication, resources, disposition, and bureaucratic structure. Research data were obtained through primary and secondary data using data collection techniques such as observation, in-depth interviews, and documentation, then analyzed qualitatively. The results showed that PKH implementation in Curahmalang Village was influenced by these four factors. From the communication aspect, information delivery, clarity, and consistency of communication were considered quite good due to the role of facilitators in bridging the government with beneficiaries. In terms of resources, the availability of facilitators and information was adequate, but the utilization of facilities, especially health facilities, was not fully optimal because some beneficiaries did not utilize them according to their needs. The disposition aspect shows that the implementer's attitude and compliance towards Beneficiary Families (KPM) are relatively good, although some participants are still less committed to fulfilling program obligations. Meanwhile, in the aspect of bureaucratic structure, weaknesses were found, particularly in terms of coordination and cooperation between PKH facilitators and the village government, which has not been running optimally, thus impacting the effectiveness of work patterns.